Faktor Utama dalam Menumbuhkan Pembelajaran Bermutu di Sekolah Menengah Kejuruan Teknologi - Ungsi Antara Oku Marmai (Universitas Negeri Malang, 2016)
The lecturer's attitude, the student's attitude in learning, and the quality of instructional setting are very strategic to produce qualified graduates in labor market. Therefore, researches on those factors should be increased in the future. Several teacher's attitudes identified in this article will improve the quality of instructions in vocational senior high schools. Those attitudes and their implications to instruction will be discussed in this article. Those three factors should be known and applied by teachers and students so that their teaching and learning outcomes will be optimum